The effect of selenium supplementation on oxidative stress, clinical and physiological symptoms in patients with migraine: a double-blinded randomized clinical trial - Balali, Arghavan; Sadeghi, Omid; Khorvash, Fariborz; Rouhani, Mohammad Hossein; Askari, Gholamreza (Frontiers in Nutrition, 2024)
Background and Aim The present double-blinded randomized clinical trial aimed to investigate the effect of selenium supplementation on oxidative stress, clinical, and physiological symptoms in patients with migraine. Methods In total, 72 patients with migraine were randomly assigned to receive either 200 μg/day selenium (n = 36) or placebo (n = 36) for 12 weeks. Clinical traits of migraine (e.g., severity, frequency, and duration of headaches), mental health indices (e.g., depression, anxiety, and distress), quality of life, biomarkers of oxidative stress (e.g., nitric oxide [NO], malondialdehyde [MDA], total antioxidant capacity [TAC], total oxidant status [TOS]), and anthropometric indices were assessed at baseline and at the end of the study. Results Selenium supplementation resulted in a significant reduction in NO (−1.24 ± 0.43 vs. 0.16 ± 0.43; p = 0.03) levels and a significant increase in TAC (9.89 ± 2.50 vs. −0.18 ± 2.50; p = 0.01) compared to the placebo group. Moreover, selenium supplementation had a significant protective effect against MDA levels compared to placebo (0.33 ± 0.57 vs. 1.83 ± 0.57; p = 0.03). In addition, selenium intake was associated with a lower headache frequency (−8.15 ± 0.77 vs. −4.12 ± 0.77; p < 0.001) and severity (−2.89 ± 0.42 vs. −1.16 ± 0.42; p = 0.01) as well as a lower Headache Impact Test-6 (HIT-6) score (−9.22 ± 2.00 vs. −2.08 ± 2.00; p = 0.02) compared to the controls. For other outcome variables, we found no significant effect. Conclusion Selenium supplement may be considered a complementary therapy in patients with migraine due to its beneficial effects on oxidative stress and migraine symptoms. Further studies are needed to affirm our findings. Clinical Trial Registration: This study was registered in the Iranian Registry of Clinical Trials (https://www.irct.ir) on 27 May 2023 with code number of IRCT20121216011763N60.